EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) DENGAN PENDEKATAN PROBLEM SOLVING DITINJAU DARI AKTIVITAS BELAJAR SISWA - Ignatius Dono Arianto (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aim of the research was to determine the effect of learning models on learning achievement viewed from the student learning activity. The learning models compared were cooperative learning STAD with problem solving approach, cooperative learning STAD and conventional learning. The type of the research was a quasi-experimental research. The population was the students of high school in Merauke regency on academic year 2012/2013. The size of the sample was 291 students consisted of 98 students in the first experimental group, 100 students in the second experimental group and 93 students in the control group. The instruments used were questionnaire, and learning achievement test. The data was analyzed using analysis of variance. The conclusions of the research were as follows. (1) STAD with problem solving approach gives better learning achievement than STAD and conventional, and STAD gives better learning achievement than conventional. (2) The students with high learning activity have better learning achievement than the students with middle and low learning activity, and the students with middle learning activity have better learning achievement than the students with low learning activity. (3) For students with high learning activity, both STAD with problem solving approach and STAD, STAD and conventional give the same effectiveness, but STAD with problem solving approach is better than conventional. In the meantime, for students with middle and low learning activity, all learning models give the same effectiveness. (4) For using of STAD with problem solving approach and conventional, both the students with high and middle learning activity, the students with middle and low learning activity have the same learning achievement, but the students with high learning activity have better learning achievement than the students with low learning activity. In the meantime, for using of STAD, all students learning activities have the same learning achievement.Key words: Student Teams Achievement Divisions (STAD), problem solving approach, student learning activity, learning achievement.